Telaah Yuridis terhadap Pembiayaan Perumahan Melalui Akad Musyarakah Mutanaqisah (MMQ) Sebagai Alternatif Pembiayaan Perumahan dalam Upaya Pengembangan Produk Perbankan Syariah - Lastuti Abubakar; Tri Handayani (Jurnal Hukum Ekonomi Islam, 2018)
Housing is a human basic need, which is from year to year increasing, while the power of people ability to purchase is not always high. Islamic banking has an opportunity to provide alternative Housing finance through Musharaka Mutanaqisah (MMQ) agreement, It is financing based on shared ownership between banks and customers. In the implementation, financing through this MMQ faces the regulatory hurdles that need to be anticipated. The solution is Indonesia must be prepared a renewal and rearrangement of regulation that are comprehensive and integrated to eliminate the disharmony and the regulatory barriers that arise in the implementation of MMQ agreement as an alternative to housing finance.. Keywords: Housing finance, Musharaka Mutanaqisah, sharia banking product development. Abstrak Kebutuhan perumahan terus meningkat, sementara daya beli masyarakat masih. Perbankan syariah berpeluang untuk menyediakan alternatif pembiayaan perumahan berdasarkan prinsip syariah melalui Musyarakah Mutanaqisah (MMQ) yakni pembiayaan berbasis kepemilikan bersama antara bank dan nasabah. Dalam implementasinya, pembiayaan MMQ ini menghadapi hambatan regulasi yang perlu di antisipasi. Diperlukan pembaruan dan penataan regulasi untuk menghilangkan disharmoni dan kendala regulasi dalam implementasi akad MMQ sebagai alternatif pembiayaan perumahan. Kata kunci: pembiayaan perumahan- Musyarakah Mutanaqisah- pengembangan produk perbankan syariah.